Traumatic spleen rupture diagnosed during postmortem dissection: A STROBE-compliant retrospective study - Fomin, Dmitrij (Medicine (Baltimore), 2019)
Spleen is typically injured in blunt abdominal trauma. Spleen injuries make 42% of all blunt abdominal injuries. The aim of this study was to perform a retrospective assessment of the cases of acute and subacute isolated traumatic spleen ruptures. A retrospective study performed on 50 patients, whose cause of death was isolated spleen rupture and bleeding into the abdominal cavity. An acute spleen rupture was diagnosed in 47 cases, whereas the rest 3 cases demonstrated a subacute rupture. In cases of acute spleen rupture, the mean weight of spleen was 309.6 g, whereas in 3 cases of subacute rupture the mean weight of the organ achieved 710 g. The mean weight of spleen in the control group with no spleen rupture was 144.7 g. Recording of the cases of isolated acute and subacute traumatic spleen ruptures and morphological assessment of them are important in forensic pathology science and in clinical practice as well.